Source: Official Guide for GMAT Review 2016 Problem Solving; #83

2

If xy ? 0 and x^2 y^2 – xy = 6, which of the

If xy ? 0 and x^2 y^2 – xy = 6, which of the following could be y in terms of x?

2 Explanations

2

Rob

Use u-substitution
xy(xy-1)=6
u=xy
u(u-1)=6
u^2-u-6=0
(u-3)(u+2)=0
u=3 or -2
xy=3 or -2
y=3/x or -2/x

May 17, 2017 • Comment

1

Jeffrey Braganza

x^2 y^2 – xy = 6
x^2 y^2 – xy - 6 = 0
Solving above eq. we get:
(xy - 3)*(xy+2) = 0
xy = 3 & xy = -2
Y=3/x & y = -2/x

Ans: II & III only

Jan 2, 2016 • Comment

priyanshi jain

Thanks Jeffrey. Really helped.

Apr 22, 2016 • Reply

Add Your Explanation

You must have a Magoosh account in order to leave an explanation.

Learn More About Magoosh

Official GMAT Material

Official Guide for GMAT Review 2016

Official Guide for the GMAT 2015 14th Ed.

Official Guide for the GMAT 13th Ed.

Official Guide for the GMAT 12th Ed.

Revised GRE PDF 2nd Ed.


Section 5.3 Problem Solving

Improve Your Score

Magoosh GMAT is an affordable online course for studying the GMAT.

Learn More About Magoosh

Share Post

Email

Facebook